2020
DOI: 10.1002/mp.14476
|View full text |Cite
|
Sign up to set email alerts
|

Using in vivo EPID images to detect and quantify patient anatomy changes with gradient dose segmented analysis

Abstract: Purpose To investigate the utility of gradient dose segmented analysis (GDSA) in combination with in vivo electronic portal imaging device (EPID) images to predict changes in the PTV mean dose for patient cases. Also, we use the GDSA to retrospectively analyze patients treated in our clinic to assess deviations for different treatment sites and use time‐series data to observe any day‐to‐day changes. Methods In vivo EPID transit images acquired on the Varian Halcyon were analyzed for simulated errors in a phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Using the first fraction image, the high‐dose low‐gradient region of the images was selected using the gradient dose segmented analysis (GDSA) technique outlined in Steers et al. which demonstrated that the GDSA technique is able to identify patient anatomy changes 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the first fraction image, the high‐dose low‐gradient region of the images was selected using the gradient dose segmented analysis (GDSA) technique outlined in Steers et al. which demonstrated that the GDSA technique is able to identify patient anatomy changes 25 …”
Section: Methodsmentioning
confidence: 99%
“…Using the first fraction image, the high-dose low-gradient region of the images was selected using the gradient dose segmented analysis (GDSA) technique outlined in Steers et al which demonstrated that the GDSA technique is able to identify patient anatomy changes. 25 The dosimetric impacts of anatomy changes such as patient weight loss, tumor shrinkage, and changes in bowel filling have been studied. The change in the Anatomical changes will also affect the shape of the distribution of relative pixel values.…”
Section: In Vivo Epid Approachmentioning
confidence: 99%
“…Additionally, detecting changes in machine output can be achieved by averaging these metrics for all patients treated on a given day and tracking over time. 14 …”
Section: Introductionmentioning
confidence: 99%
“…This work illustrated the use of the GDSA method to provide a simple metric to compare transit EPID images to predict changes in mean PTV dose (PTV D mean ) for detecting treatment errors, as well as the patient changes over the course of treatment. Additionally, detecting changes in machine output can be achieved by averaging these metrics for all patients treated on a given day and tracking over time 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation